2021
DOI: 10.1021/jacs.1c08860
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring and Modulating mtDNA G-Quadruplex Dynamics Reveal Its Close Relationship to Cell Glycolysis

Abstract: The mitochondrial DNA G-quadruplex (mtDNA G4) is a potential regulatory element for the regulation of mitochondrial functions; however, its relevance and specific roles in diseases remain largely unknown. Here, we engineered a set of chemical probes, including MitoISCH, an mtDNA G4-specific fluorescent probe, together with MitoPDS, a mitochondria-targeted G4-stabilizing agent, to thoroughly investigate mtDNA G4s. Using MitoISCH to monitor previously intractable dynamics of mtDNA G4s, we surprisingly found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 58 publications
0
33
0
Order By: Relevance
“…NMM, ThT, metal complexes, and other organic molecules, which are weakly fluorescent in aqueous solution, can be bound with G4 with significant enhancement of fluorescence intensity. Therefore, the enhancement of fluorescence intensity has been useful for the visualization of G4. ,,,,,, ,,, In 2015, Myong et al constructed a double-strand probe binding NMM and crystal violet for G4 formation . In dsDNA, the possibility of G4 formation is significantly reduced because of competition between paired bases.…”
Section: Gfs Noncovalently Modified With Extrinsic Fluorogenic Dyesmentioning
confidence: 99%
“…NMM, ThT, metal complexes, and other organic molecules, which are weakly fluorescent in aqueous solution, can be bound with G4 with significant enhancement of fluorescence intensity. Therefore, the enhancement of fluorescence intensity has been useful for the visualization of G4. ,,,,,, ,,, In 2015, Myong et al constructed a double-strand probe binding NMM and crystal violet for G4 formation . In dsDNA, the possibility of G4 formation is significantly reduced because of competition between paired bases.…”
Section: Gfs Noncovalently Modified With Extrinsic Fluorogenic Dyesmentioning
confidence: 99%
“…To date, about 3000 different G4-targeted ligands have been identified based on the collection of the G4LDB website, and they differ in selectivity, affinity, binding sites, and cellular permeability. Among them, pyridostatin [PDS (4-(2-aminoethoxy)- N 2 , N 6 -bis­(4-(2-aminoethoxy)­quinolin-2-yl)­pyridine-2,6-dicarboxamide)] and its derivatives [ e.g. , PyPDS (4-(2-aminoethoxy)- N 2 , N 6 -bis­(4-(2-(pyrrolidin-1-yl)­ethoxy)­quinolin-2-yl)­pyridine-2,6-dicarboxamide)] first reported by Balasubramanian’s group are particularly outstanding in the G4 studies due to their high specificity and affinity for G4s. , PDS and PyPDS have been widely used as highly specific G4-binding agents combined with different functional modules and technologies to decipher and regulate the biological functions of G4s, for example, to visualize individual DNA G4 formation in live cells, to visualize monogenic RNA G4s in single cells, to map G4 distribution in the human genome, to investigate chemical profiling of G4-interacting proteins in cells, , and so forth. Although plenty of work has been done to study the interactions between PDS/PyPDS and G4s, the structural information of PDS/PyPDS–G4 complexes remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Ribonucleic acid (RNA) as a vital component of the Central Dogma has been well recognized for its roles in transcription and translation. RNA interference (RNAi) technology has proved to be a promising modality for cancer and other disease treatments by silencing the target gene expression. Thus far, two types of RNAi therapeutic strategies have been developed to silence the RNA molecules that are associated with certain diseases by utilizing antisense oligonucleotides and small molecules. , However, their promise for clinical application is greatly impeded by low delivery efficiency, susceptibility of RNA to serum RNases, poor gene silencing activity due to noncovalent interaction, and potential systemic toxicity. Numerous studies have recently demonstrated that the covalent modification of RNA strands can disturb the function of targeted RNA, leading to dysregulated expression of downstream proteins that may impact various cellular processes, which has been considered to be a promising approach for gene silencing. Op de Beeck and Madder have previously reported a photo-induced cross-linking method to study the intermolecular interaction of DNA–DNA and protein–DNA through the 1 O 2 -initiated cycloaddition reaction between furan and nucleobases of DNA under the oxidation of 1 O 2 generated from methylene blue excited by visible light .…”
Section: Introductionmentioning
confidence: 99%